Rans and detached-eddy simulation of the NASA trap wing for HILIFTPW-1. - Wang, Zhongyuan (Cranfield University, 2018)
This project aims to study and perform a turbulent flow simulation over the NASA Trap Wing by exploring the numerical aerodynamic predictions capacity of high lift configurations using two S-A, k-ω SST and DES method for comparison in ANSYS Fluent software, among which DES method has been paid key attention for its accuracy as a CFD high lift prediction tool. NASA Trap Wing geometry from High lift Prediction Workshop-1 is applied in this project with slat angle of 30° and flap angle of 25°. Prediction results are analysed for several flow characteristics including pressure distribution, force and moment coefficient as well as skin friction and some other flow visualization. Results show that the DES method performs the best flow prediction near stall, however, it fails to provide as good flow characteristics at low pitch angles as S-A model and fails to show stall patterns. Both S-A and k-ω SST model shows a premature stall due to massive separation at high AoAs, while k-ω SST model gives a worst prediction results among all the three turbulent models applied. Restarted S-A model, based on experience from the 1st AIAA High lift Prediction Workshop, means high pitch angle case restarted with the converged solution of lower pitch angle case, which improves the prediction results of original S-A model by delaying the separation in very limited extent. Further researches have been proposed including key local mesh adaption, further application of URANS model for comparison, higher AoA cases for DES model for testing its capability, increasing the pitch angles cases more gradually for better prediction.
Keywords: RANS; DES (Detached-eddy Simulation); high lift prediction workshop; NASA trap wing; stall prediction; turbulent flow